32 & 16 YEARS AGO. - Holmes, Neville (Computer (00189162), 2008)
The article presents information on issues and topics related to computers featured in the previous issues of "Computer." In April 1976, a report released by Arthur D. Little revealed principal social issues that require regulatory action including freedom of choice and possible misuses of electronic funds transfer (EFT). Also in April 1976, an issue focused on graphic terminals which allow on-line interaction between the user and his program, thus enabling him to change the displayed image according to his preferences. In an April 1992 issue, it was reported that CalComp Digitizer Products Group has developed DisplayPad, which allows users to turn a standard desktop or portable computer into a pen-based system.